Effect of the www.dailyesl.com website as a technological and pedagogical resource fot teaching english at El Flor Elementary School, 2015 - Caballero Guerra, Stephanie (David, Panamá: UDELAS, 2015)
Panamá is recognzed internationally as a center of business trade, and the best country of mCentral America for tourism. Regarding these aspects, it can be said that most of the negotiations are handle in English language and that ost of the tourist that come also use English as the lingua franca.
TABLE OF CONTENT GRAPHIC INDEX CHART INDEX INTRODUCTION CHAPTER 1: ANTECEDENTS AND STATEMENT OF THE PROBLEM 1.1. Antecedents 1.2. Statement of the problem 1.3. Objectives 1.3.1. General objectives 1.3.2. Specific objectives 1.4. Justification 1.5. Scope and delimitation CHAPTER II: THEORETICAL FRAMEWORK 2.1. Theoretical framework 2.2. Technology in the schools 2.3. Effectiveness of technology as instructional tool 2.4. Technology to teach english as a second or foreign language 2.4.1. Computer use in teaching 2.5. Computer assisted language learning (CALL) 2.6. Computer oriented activities 2.6.1. Teachers and confidence with CALL 2.6.2. Advantages of applying CALL to teach english 2.6.3. Websites to teach english 2.7. Skills acquired by students when learning english with the help of dailyesl.com webside 2.8. Oral communicative problems solved through the english teaching website dailyesl.com CHAPTER III: METHODOLOGICAL ASPECTS 3.1. Type of research 3.1.1. Qualitative research 3.1.2. Quantitative research 3.1.3. Demographic research 3.2. Research desing 3.2.1. Quasi experimental desing 3.3. Sources of information 3.4. Subjects 3.4.1. Sample 3.5. Variable 3.5.1. Dailyesl.com webside 3.5.1.1. Conceptual definition 3.5.1.2. Operational definition 3.5.1.3. Instrumental definition 3.5.2. Students english oral communicative skills 3.5.2.1. Conceptual definition 3.5.2.2. Operational definition 3.5.2.3. Instrumental definition 3.5.3. Studens´attitude toward CALL 3.5.3.1. Conceptual definition 3.5.3.2. Operational definition 3.5.3.3. Instrumental definition 3.5.4. Teachers attitude toward CALL 3.5.4.1. Conceptual definition 3.5.4.2. Operational definition 3.5.4.3. Instrumental definition 3.6. Hypothesis 3.7. Description of data collection instruments 3.7.1. English oral skill proficiency test 3.7.2. Students structured survey 3.7.3. Teachers' semi.-structured survey 3.8. Treatment of the information CHAPTER IV: ANALYSIS OF RESULTS 4. Analysis of results CONCLUSIONS RECOMMENDATIONS REFERENCES ANNEX
Incluye Graphic index
Incluye chart index
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; PEDAGOGICAL RESOURCE -- TESIS DE LICENCIATURA; LICENCIATURA EN DOCENCIA EN INGLÉS; WWW.DAILYESL.COM; EL FLOR ELEMENTARY SCHOLOL; ESCUELA DE PEDAGOGÍA DOCENCIA DE INGLÉS